Field evaluation of Fusarium tumidum as a bioherbicide against gorse and broom - Fr?hlich, J.; Zabkiewicz, J.A.; Gianotti, A.F.; Ray, J.W.; Vanner, A.L.; Liu, Z.Q.; Gous, S. (New Zealand Plant Protection, 2000)
Fusarium tumidum spores formulated in water and three invert emulsions were tested under field conditions as a potential bioherbicide against gorse (Ulex europaeus) and broom (Cytisus scoparius) Inundation with F tumidum spores failed to induce severe disease epidemics The invert emulsion formulants demonstrated some phytotoxicity towards gorse and Pinus radiata Plant species and age spore concentration and application rate all influenced the performance of the bioherbicide formulations It will be necessary to develop further formulations that will better enhance the activity of F tumidum in the field